Peningkatan Kemampuan Menjumlahkan Bilangan Pecahan Melalui Media Kertas Lipat Pada Siswa Kelas V SD Inpres Wairotan - Fransiska Esty Astika Nau; Maria Angelina Fransiska Mbari; Marianus Yufrinalis (Journal on Education, 2023)
This study aims to improve student learning outcomes by applying folding paper learning media. This research is a classroom action research (PTK) designed to help teachers (researchers) find and solve learning problems that occur in the classroom. This class action research will be carried out in a cyclical manner, between cycle I and cycle II. The results showed that after giving action for two cycles the average score of the test results increased learning outcomes by applying learning media Kertas Lipat in Mathematics subjects increased. Cycle I resulted in a score of 65% with the category not meeting the Minimum Completion Criteria (KKM). In cycle II, it experienced a very significant increase of 91.3% and met KKM. This shows that student learning outcomes in Mathematics subjects can be further applied to improve student learning achievement, especially in Mathematics subjects summing fractional numbers. The use of Folding Paper media can improve the learning outcomes of grade V students of SD Inpres Wairotang.